Case Report: Variegate porphyria disclosed by post-gastric bypass complications and causing predominant painful sensorimotor axonal peripheral neuropathy - Collaud, Edwige; Wittwer, Luis; Minder, Anna-Elisabeth; Annoni, Jean-Marie; Minder, Elisabeth I.; Chabwine, Joelle N. (Frontiers in Genetics, 2022)
BACKGROUND AND AIMS: Porphyrias constitute a group of rare genetic diseases due to various, mostly autosomal dominant mutations, causing enzymatic deficiency in heme biosynthesis. As a result, neuro-toxic porphyrin precursors and light-sensitive porphyrins accumulate, while their targets determine the disease symptoms. Porphyria variegate (VP), one of the acute hepatic porphyrias, is caused by a protoporphyrinogen oxidase (PPOX) mutation. During acute crisis triggered by drugs, stressors or fasting, an increase of porphobilinogen (PBG), aminolaevulinic acid (ALA) and porphyrins in urine and stool occur, damaging the autonomous, peripheral and central nervous system. The disease remains often latent life-long, or displays minimal symptoms usually overlooked. We present here an unusual constellation of precipitating factors. CASE REPORT: This 46-year-old woman presented, some days after a gastric by-bass surgery, with severe flaccid tetraparesis and neuropathic pain, initially misdiagnosed as a functional neurological disorder. The severe sensorimotor polyneuropathy led to further investigations, disclosing high urinary PBG, ALA and porphyrin levels due to a new PPOX mutation. Retrospectively, the patient had had typical VP symptoms (abdominal pain, fragile skin, dark urines) for years prior to surgery. With carbohydrate load, neurorehabilitation and analgesics, she slowly recovered to full mobility, partial autonomy in her daily life activities, although pain persisted. CONCLUSION: This case documents porphyria as an exceptional complication after gastric by-bass surgery, suggesting that screening for cardinal symptoms or a family history prior to any treatment influencing the diet could prevent porphyria crises and their irreversible adverse consequences in patients with latent or minimally symptomatic undiagnosed porphyria.